Sports venue digital twin technology from a spectator virtual visiting perspective - Glebova, Ekaterina; Book, Robert; Su, Yiran; Perić, Marko; Heller, Jonas (Frontiers in Sports and Active Living, 2023)
The purpose of this article is to adopt a customer-centric perspective the and introduce digital twin technology as a solution for mega-sport event management. This conceptual model article focuses on the potentially drastic role of digital twin technology in modern sports events, explaining in detail different aspects of its impact. The main research question is "How (and why) do sports venue digital twin emerging technologies prospectively impact the sports spectators' customer experiences?" It contributes to understanding how and why sports venue digital twins make events more customer-centred by enhancing fan experiences and engagement. Subsequently, it aims to position digital twin technology as an innovative solution for mega-sport event management across various customer experience touchpoints.By examining the intersection of digital twins and sports events from a customer-centric lens, this article will elucidate the intricacies involved in leveraging this emerging technology to transform stakeholder and fan experiences at major sporting events. Finally, we outline and explain the obstacles, challenges, opportunities, and perspectives of digital twin technology at an intersection with sports events from a customer-centric perspective. The use of digital twins potentially enables the creation of hyper-realistic virtual replicas of sports venues, providing immersive and personalized experiences for spectators. This technology allows event organizers to optimize resource allocation, streamline logistics, and improve operational efficiency.